Pengetahuan Prosedural dan Korelasinya dengan Pengetahuan Konseptual Mahasiswa pada Topik Genetika Populasi Berbasis Molekuler - Murni, Dewi Murni; Amelia, Evi; Lestari, Ling Dwi; Suryaningsih, Septionita; Indriyani, Riza; Zahra, Intan Az (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2024)
Procedural knowledge is one dimension of knowledge that has an important role, which is to help students acquire conceptual knowledge. Procedural knowledge helps students understand concepts in the Genetics Course, including